1975
DOI: 10.1073/pnas.72.12.5056
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic observations on the meiotic karyotype of diploid and tetraploid Saccharomyces cerevisiae.

Abstract: Certain strains of Saccharomyces cerevisiae contain visible segments of synaptonemal complex which are apparent components of bivslents in pachytene of meiotic prophase. The synaptonemal complex has the typical width in the frontal plane but is unusually thin in the sagittal plane, thus accounting for its poor visibility. Amorphous densities situated adjacent to the central element occur at intervals suggesting their coincidence with sites of crossing over. Reconstruction of the synaptonemal complex from seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(92 citation statements)
references
References 18 publications
8
84
0
Order By: Relevance
“…These studies have shown that at pachytene, homologous chromosomes are held in register by a continuous synaptonemal complex from telomere to telomere revealing an apparently specific site-to-site matching of homologous regions. Both light and electron microscopical studies agree in that the number of irregularities is surprisingly low (2,4,6,9,13,14,16,22,33). Furthermore, it has been demonstrated that prior to the onset of pairing, homologous chromosomes are either located at random in the nucleus (1 i, 12, 22, 25) or in separate nuclei (4, 0105-1938/79/0044/0101/$ 05.00 32, 33) the only exception being organisms with a permanent somatic pairing of homologous chromosomes.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…These studies have shown that at pachytene, homologous chromosomes are held in register by a continuous synaptonemal complex from telomere to telomere revealing an apparently specific site-to-site matching of homologous regions. Both light and electron microscopical studies agree in that the number of irregularities is surprisingly low (2,4,6,9,13,14,16,22,33). Furthermore, it has been demonstrated that prior to the onset of pairing, homologous chromosomes are either located at random in the nucleus (1 i, 12, 22, 25) or in separate nuclei (4, 0105-1938/79/0044/0101/$ 05.00 32, 33) the only exception being organisms with a permanent somatic pairing of homologous chromosomes.…”
Section: Introductionsupporting
confidence: 55%
“…These data show that an increase in ploidy level is not accompanied by a comparable increase of the total length of the lateral components as is the case in di-and tetraploid yeast (2). In the diploid Bombyx oocytes, the lateral component length for the individual genome at early pachytene is 196 ~m, that for triploid oocytes 137 ram and or more interlockings) and in tetraploid oocytes (one interlocking in 7 early pachytene nuclei).…”
Section: Chromosome Length and Chromosome Pairingmentioning
confidence: 71%
“…The RNs of D. lacteum are small spherical structures, not exceeding 70 nm in diameter. They therefore occupy the lower end of the observed range of RN sizes and are comparable to the rather small RNs which characterise many fungal species (e.g., Byers and Goetsch, 1975;HoIm et al, 1981).…”
Section: Electron Microscopy Pachytene Scsmentioning
confidence: 97%
“…lacteun and has been encountered, for example, for the small RNs of yeast (Byers and Goetsch, 1975) ellipsoid nodules of wild-type Drosophila oocytes (Carpenter, 1981), spherical and ellipsoid RNs of some meiotic mutants of Drosophila (Carpenter, 1979b) and zygotene RNs in the fungus Coprinus (Hoim et a!., 1981). In D. lacteum the problem is compounded by the dense central element of the SC which makes it difficult to detect with certainty any but the largest and most prominent RNs.…”
Section: Electron Microscopy Pachytene Scsmentioning
confidence: 99%
“…The tripartite structure of the synaptonemal complex is remarkably uniform in eukaryotes, although the ratio of synaptonemal complex length to DNA length ranges from 1: 100 in yeast (Byers and Goetsch, 1975) to l'5 : 10,000 in maize (Gilles, 1973). The lateral elements are proteinaceous rods with a diameter of 300 A-600 A which may contain RNA (Westergaard and von Wettstein, 1970;Esponda and Stockert, 1971) and histones (Strokov et al, 1973).…”
Section: The Synaptonemal Complexmentioning
confidence: 99%